COMPETENCE ASSESSMENT OF AIR TRAFFIC CONTROL PERSONNEL - Luppo, Alexander; Rudnenko, Veronika (Proceedings of National Aviation University (archive), 2012)
The article deals with the main principles of competence assessment of Air Traffic Control personnel, including performance objectives and methods of assessment.